Pertanggungjawaban Pidana Pelaku Tindak Pidana Perdagangan Wanita - Salim, Syukri Niam; Widarto, Bambang; Sudarto, Sudarto (Neolectura, 2025)
Trafficking in persons is a crime that violates human rights because it involves threats, coercion, abduction, fraud, abuse of power, and aims at prostitution, pornography, violence, exploitation, forced labor, or slavery. The Criminal Code imposes relatively light sanctions that are disproportionate to the impact on victims, so a special law is required to provide both material and formal legal basis. This study applies a normative juridical research method by examining relevant legislation and court decisions. The findings show that trafficking in persons is regulated in Article 297 of the Criminal Code in conjunction with Article 65 of Law No. 39 of 1999 and Articles 2, 4, 11, and 48 paragraph (1) of Law No. 21 of 2007. Criminal liability of perpetrators of women trafficking is enforced through a three-year prison sentence as stipulated in Article 2 paragraph (1) of Law No. 21 of 2007, accompanied by a fine, as the defendant was proven legally and convincingly guilty. This research emphasizes the need for new specific laws, government regulations, and ministerial decrees to clarify legal arrangements, provide greater protection for victims, and ensure heavier sanctions for perpetrators.